Nisbah Kelamin Jantan dan Betina yang Berbeda terhadap Kinerja Pertumbuhan dan Reproduksi Ikan Nila Merah (Oreochromis niloticus) - Rahawarin, Monika; Mainassy, Desti Milen; Madidi, Yehenka; Sahusilawane, Helena Afia (JARI : Jurnal Akuakultur Rawa Indonesia, 2025)
Red tilapia (Oreochromis niloticus) is a freshwater fish species with high economic value, making it a superior commodity. Tilapia consumption has increased significantly from year to year so that optimal cultivation efforts are needed. However, in its cultivation, there are constraints on growth and reproduction performance that are determined by the ratio of males and females. Male tilapia tend to grow faster and mature faster than females. Thus, male tilapia can be used to increase and control productivity. So far, research on monosexed and mixed rearing of male and female red tilapia has not been conducted. This study aims to prove the effect of sex ratio on growth and reproduction performance in an effort to increase the productivity of red tilapia. This study used a completely randomised design (CRD) with sex ratio treatment of male (100%), male:female (25%:75%), male:female (50%:50%), male:female (75%:25%); female (100%) in broodstock repeated three times. The stages of this study consisted of collection of broodstock samples, broodstock rearing in single and mixed populations (according to treatment), observation of growth performance (total length, standard length, body width, body weight, daily growth rate, broodstock survival) and reproductive performance (number of larvae, larval size, larval survival) during 1 month of rearing.